Nuovamente la Biennale di Paesaggio di Barcellona. Dialogo con Jordi Bellmunt - Dall’Ara, Enrica (Ri-Vista. Research for landscape architecture, 2015)
First reflections on the fourth Biennal of Landscape Architecture, after few days from the end of the meeting, in a dialogue with Jordi Bellmunt ,director of the Master Programme in Landscape Architecture and member of the Biennal Esecutive Committee. These considerations are anticipated by a brief history of the event. The results of Rosa Barba Prize, the projects chosen for the exposition and the finalist projects, the theme of this edition Landscape: product/production, all these things originates a reflection, by one side, on the value of research and innovation in the landscape project and, by the other side, on the importance of a spread good doing in the profession (good practices that can tent to standardization).